Extradural Corticosteroid Injection in Management of Lumbar Nerve Root Compression. Issue 5867 (16th June 1973) - Dilke, T. F. W.; Burry, H. C.; Grahame, R.
Abstract : The effect of extradural corticosteroid injection in patients with nerve root compression syndromes associated with degenerative disease of the lumbar intervertebral discs was assessed in a double-blind controlled trial on 100 consecutive inpatients assigned by random allocation to treatment and control groups. Assessment during admission and at three months revealed statistically highly significant differences in respect of relief of pain and resumption of normal occupation in favour of the group treated by extradural injection. This treatment seems to be a valuable adjunct to the management of lumbar nerve root compression syndromes associated with degenerative disc disease.